2002
DOI: 10.1038/ng951
|View full text |Cite
|
Sign up to set email alerts
|

The transcriptional program of meiosis and sporulation in fission yeast

Abstract: Sexual reproduction requires meiosis to produce haploid gametes, which in turn can fuse to regenerate a diploid organism. We have studied the transcriptional program that drives this developmental process in Schizosaccharomyces pombe using DNA microarrays. Here we show that hundreds of genes are regulated in successive waves of transcription that correlate with major biological events of meiosis and sporulation. Each wave is associated with specific promoter motifs. Clusters of neighboring genes (mostly close … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

55
653
1
14

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 460 publications
(723 citation statements)
references
References 29 publications
55
653
1
14
Order By: Relevance
“…Cufflinks was used to assemble mapped reads into the final transcriptome and to calculate Fragments Per Kilobase of transcript per Million (FPKM) mapped reads. Genes were classified as either meiotic or non-meiotic 43 . The Area proportional Euler Venn diagram for meiotic gene overlap was constructed using EulerAPE.…”
Section: Methodsmentioning
confidence: 99%
“…Cufflinks was used to assemble mapped reads into the final transcriptome and to calculate Fragments Per Kilobase of transcript per Million (FPKM) mapped reads. Genes were classified as either meiotic or non-meiotic 43 . The Area proportional Euler Venn diagram for meiotic gene overlap was constructed using EulerAPE.…”
Section: Methodsmentioning
confidence: 99%
“…pombe cells have revealed that the genes involved in sporulation are periodically expressed in four successive waves (Mata et al, 2002). The first wave is a response to nutrient deprivation; the second, or early, wave occurs during the premeiotic S phase; the third, or middle, wave corresponds to meiosis I and II; and, the fourth, or late, wave coincides with ascospore formation.…”
Section: Introductionmentioning
confidence: 99%
“…Among the genes induced during the middle and late waves are those encoding enzymes involved in the synthesis of the ascospore wall, such as chitin synthase Chs1p, putative chitin deacetylase Cda1p, β-glucan synthase Bgs2p, and α-glucan synthases Mok12p and Mok13p (Arrelano et al, 2000;Liu et al, 2000;Martín et al, 2000;Garciá et al, 2006;Matsuo et al, 2005). Interestingly, the gene encoding the paralogue of the characterized endo-(1,3)-α-glucanase Agn1p, Agn2p, is also highly upregulated during the middle phase (Mata et al, 2002). Recently, we showed that, although also expressed during vegetative growth, agn2 + appears to function during sporulation (Dekker et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Class 4, for example, is clearly the class that contains the noisiest spot regions while class 3 contains spots that are in high contrast to their background. Not only has the iterative training approach detected the number of classes (9) to divide the many spot regions within an image into, but it has also provided a means to classify quickly a given spot region into one of the 9 classes.…”
Section: Spot Classifiermentioning
confidence: 99%